PROCEDURE FOR FUNDRAISING OF ZAKAT, INFAQ, SHODAQOH AND WAKF BEFORE AND AFTER PPKM AT YATIM MANDIRI FOUNDATION SIDOARJO - Aira Vema Mutiara Nausan; Susilowati (ICO EDUSHA, 2021)
The amil zakat agency/institution is the party that has the right to manage ZISWAF (Zakat, Infaq, Shodaqoh and Waqf) funds which are expected to help solve the problem of poverty and social inequality in society. Among the many amil zakat institutions or LAZ, Yatim Mandiri Foundation, where one of its branches in Sidoarjo has become a place for Field Work Practices (PKL) for students. The Field Work Practice (PKL) activity which development method of this system used descriptive qualitative analysis by obtaining a systematic description and data about the procedures for receiving zakat funds, infaq shodaqoh and waqf at the Yatim Mandiri Sidoarjo Foundation. From the Field Work Practice (PKL) activities at YATIM MANDIRI, it can be concluded that the Yatim Mandiri Amil Zakat Institution has a function and role in improving the education and economy of orphans and poor people. Furthermore, they have the responsibility to manage and collect funds from the community to be distributed to those in need. In good condition, whether before or after PPKM, Yatim Mandiri always made it easy for everyone who wanted to become a benefactor. Keywords: Yatim Mandiri, Funds, Zakat, Infaq, Shodaqoh, Waqaf References Berita diakses dari www.yatimmandiri.org Pada tanggal 20 Juli 2021 Brosur Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021. Surabaya Cholisoh, Nur. 2011. Peran Badan Amil Zakat (BAZ) dan Implikasi Zakat, Infaq, Shadaqah (ZIS) terhadap Peningkatan Kesejahteraan Studi Kasus BAZ Kota Malang. Skripsi tidak diterbitkan. Malang: Universitas Brawijaya. Hafidhuddin, Didin. 1998. Panduan Praktis Tentang Zakat Infak Sedekah. Jakarta: Gema Insani. Hafidhuddin. Didin. 2008. The Power of Zakat (Studi Perbandingan Pengelolaan Zakat Asia Tenggara). Malang: UIN-Malang Press. Laporan Pelaksanaan Magang UIN Syarif Hidayatullah Jakarta Majalah Lembaga Amil Zakat Nasional Yayasan Yatim Mandiri. 2021. Surabaya Merina, Dita Elia. 2017. Peran Badan Amil Zakat Nasional Dalam Upaya Menanggulangi Kemiskinan Melalui Program Bondowoso Unggulan Studi Kasus di Kabupaten Bondowoso. Skripsi tidak diterbitkan. Malang: Universitas Brawijaya.